Contribution of soil quality to banana yield problems and its relation with other banana yield loss factors - Asten, Piet J.A. van; Gold, C.; Wendt, J.; Waele, D. de; Okech, S.; Ssali, H.; Tushemereirwe, Wilberforce K. (2005)
In Uganda, highland banana yields (5-30 t ha-1yr-1) are low in comparison to potential yields (70 t ha-1yr-1) due to high pest and disease pressure, soil fertility decline, and poor management. Although it is generally accepted that soil exhaustion is a major cause of low and declining yields, there are almost no data to demonstrate this relationship. Most studies show that banana soils are relatively fertile and often contain sufficient nutrients for optimum growth. Nonetheless, K, N and Mg deficiencies are commonly detected in fertilizer trials and banana foliar samples. The growing commercialization of banana increases the export of plant nutrients from the farms to the urban centers. Contrary to commercial production in most parts of the world, Ugandan banana growers do not use chemical fertilizers to replenish soil nutrient stocks. Instead, they rely on organic supplements, causing further soil fertility decline of annual cropped fields and grassland. Although nutrient losses can be minimized with improved organic matter management, sustaining long-term soil fertility without the use of external inputs seems unlikely. Thereis evidence showing that pest and disease pressure are closely related to soil fertility and plant nutrient uptake. However, the functional relationships between pests, diseases and soil fertility problems are yet to be resolved. When developing improved crop management options, it is necessary to address pest, disease and soil problems in an integrated way.